ANALYSIS OF THE INFLUENCE OF PRODUCT QUALITY AND SERVICE QUALITY ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION AS A MEDIATION VARIABLE FOR UD. PADMA NADI CUSTOMERS. - Putra Utama, I Putu Indra Ariestha; Kaihatu, Thomas Stefanus (International Journal of Review Management Business and Entrepreneurship (RMBE), 2025)
This study aims to determine the effect of product quality and service quality on customer loyalty through customer satisfaction with UD Padma Nadi as the research object. The variables used in this research are product quality and service quality as the independent variables, customer satisfaction as the mediating variable and customer loyalty as the dependent variable. The method used is quantitative mediation. The sample used in this study used a non-probability sampling method with a purposive sampling technique and a sample of 100 respondents. Data collection techniques in this study were carried out by distributing questionnaires using a Likert scale. Based on the results of data analysis, it can be interpreted that product quality has a significant effect on customer loyalty, product quality has a significant effect on customer satisfaction, service quality has a significant effect on customer loyalty, service quality has a significant effect on customer satisfaction, customer satisfaction has a significant effect on customer loyalty. In addition, mediation occurs in the relationship between product quality and customer loyalty through customer satisfaction, and mediation occurs in the relationship between service quality and customer loyalty through customer satisfaction.